THE IMPORTANCE OF MORPHOLOGICAL INVESTIGATIONS IN DIAGNOSTICS AND STUDY OF INFECTIONS. TISSUE MICROBIOLOGY - V. A. Zinserling (Журнал инфектологии, 2018)
The paper is based upon personal experience of the author compared with literary data includes information related to significance of life-time and postmortem morphological investigations in diagnostics and study of pathogenesis of viral, bacterial, fungal and mycoplasma infections including influenza, HIV, tuberculosis. Different clinical and pathological forms and some questions of terminology are discussed. Most difficult and unclear questions requiring further complex investigation including morphology are listed. Age given the bases to introduce new term “tissue microbiology”.